Historical Development of Islamization in the Nusantara: Trends and Scholarly Contributions - Choirin, Muhammad; Masuwd, Mowafg Abrahem; bin Yusof, Muhammed; Salim, Hakimuddin; Tanjung, Hasan Basri (Journal of Al-Tamaddun, 2025)
This study conducts a comprehensive bibliometric analysis of the historical trajectory of Islamization in the Nusantara, with a focus on tracing key scholarly contributions and academic trends over time. By applying advanced bibliometric methods, this research systematically examines a broad array of academic literature, identifying seminal works, prominent authors, and influential periods that have shaped the discourse surrounding Islamic propagation and its integration into the cultural fabric of the region. The findings highlight significant trends in the evolution of da’wah strategies, the roles of diverse actors in the dissemination of Islam, and the socio-political dynamics that have influenced these processes. Furthermore, the study offers a critical assessment of the implications of these academic patterns for contemporary da’wah efforts, suggesting that an understanding of historical scholarly contributions can enhance the relevance and effectiveness of modern da’wah initiatives. This bibliometric approach not only enriches the academic landscape of da’wah and Islamization studies but also provides a nuanced framework for future research, contributing to a more profound understanding of the Islamic historical and intellectual legacy in the Nusantara.